(untitled) (Journal of Economic Additions, 2026)
This study examines the accelerating trends and spatial concentration of global water stress under climate change using SDG indicator 6.4.2. Findings highlight intensifying scarcity in arid regions like MENA, driven by rising evapotranspiration and competing urban-agricultural demands, which elevate risks of supply disruptions and resource-based tensions. To mitigate these threats, the study advocates for integrated water governance focused on demand efficiency, expanded desalination and reuse, and the implementation of basin-level early-warning systems and drought management strategies. Jel Classification Codes : Q25 ; Q54.